Adhesive Intestinal Obstruction in Infants and Children: The Place of Conservative Treatment. (30th June 2011) - Al-Salem, Ahmed H.; Oquaish, Mohammad
Abstract : Objectives . Adhesive intestinal obstruction (AIO) is rare in the pediatric age group and its treatment is still controversial. This is a retrospective review of our experience in infants and children with AIO. Patients and Methods . The records of infants and children with AIO between January 2001 and December 2010 were retrospectively reviewed for age at diagnosis, sex, initial operation, interval between initial operation and presentation, diagnosis, treatment and outcome. Results . 44 infants and children were admitted with AIO. There were 28 males and 16 females who had 46 episodes. Their ages at presentation ranged from 1 month to 12 years (mean 5.4 years), while their ages at initial operation ranged from 2 days to 12 years (mean 4.15 years). Time elapsed from initial operation to presentation ranged from 7 days to 8 years (mean 1.5 years), and 66% developed AIO within 1 year from initial operation. Appenedecectomy was the commonest operation (29.5%). Four (9%) responded to conservative treatment. The other 40 (91%) required surgical intervention. Twenty-nine had release of adhesions only, while 10 (25%) had resection of small intestines and one underwent stricturoplasty. Two developed recurrence and one died. Conclusions . AIO is rare in the pediatric age group and the majority becomes symptomatic within 1 year of operation. Appendecectomy is the commonest operation leading to AIO. The place of conservative treatment is limited and to obviate delay and decrease the chance of intestinal ischemia, they should be treated early with surgical adhesiolysis.